PWE-116 Progression of barrett's oesophagus with low-grade dysplasia and indefinite for dysplasia. (17th June 2017) - Abradu-Berchie, B; Ragunath, K; Card, T; Robinson, L; Ilyas, M; Kaye, P
Abstract : Introduction: Background and aims: Barrett's oesophagus (BO) is a precursor for oesophageal adenocarcinoma (OAC). OAC is an important cause of mortality in the western world. This study aimed to investigate the risk of progression of indefinite for dysplasia (ID) and low-grade dysplasia (LGD) to high-grade dysplasia (HGD) or cancer (Ca) in a large cohort of BO patients under surveillance. Additionally, it aimed to investigate whether abnormal p53 expression detected through immunohistochemistry could predict neoplastic progression. Method: Methods: The histopathological reports for patients diagnosed with dysplasia or ID from January 2000 onwards were extracted. Electronic patient records were searched to identify the period of follow-up between initial endoscopy of ID or LGD to HGD/Ca. P53 immunohistochemistry was performed on cases with an initial record of ID and LGD Results: Results: Following a mean of 44.2 months of follow-up, 31 (37.3%) of the 83 LGD patients developed HGD/Ca. The annual risk of HGD/Ca for the LGD patients was 10.1% (95%CI 7.0–14.2). 2 (3.3%) out of 60 ID patients, developed HGD/Ca with a mean of 33 months of follow. The annual risk of HGD or cancer for the ID patients was 1.2% (95%CI 0.2–4.0). Patient cases positive for p53 had a greater risk of progression to HGD or OAC than those negative for p53, with a risk of 12.2% (95%CI 7.5–16.9) and 2.0% (95%CI 0.04–4.04) respectively. Conclusion: This study suggests that BO patients with LGD have a high risk of developing HGD or Cancer. Furthermore, BO patients with ID have a low risk of progression. It is of paramount importance that patients diagnosed with LGD are intensively monitored through endoscopic surveillance or treated. ID patients should also be followed up but less frequently. This study highlighted that abnormal p53 expression detected through immunohistochemistry is a stronger predictor of malignant progression than LGD. Disclosure of Interest: None Declared